Detection of Platynosomum sp. in cats in the Klang Valley, Malaysia - Nasruddin, Nur Amalina (2021)
Platynosomum sp. is a hepatic trematode causing platynosomiasis or lizard poisoning in cats through consumption or accidental ingestion of lizard, the second intermediate host of this parasite. There is little information on the detection of fluke eggs in the fecal sample and previous work only focused on stray cats with identification through post-mortem and no available information on pet cats. In general, this disease is often overlooked by veterinary practitioners due to lack of awareness and difficulty in diagnosis although the severe cases of platynosomiasis could be fatal. Therefore, the aim of this study is to determine the incidence of cat liver fluke in shelter and pet cats through fecal examination and detection in stray cats through post-mortem examination in Klang Valley, Malaysia. This study will also reveal the molecular characterization of the cat liver fluke. A total of 119 fecal samples collected from eight shelters and 82 fecal samples from veterinary clinics in Klang Valley were subjected to simple floatation and formalin-ether sedimentation technique for ova detection. From this study, Platynosomum sp. ova were identified in three fecal samples obtained from shelters (2.52%) and veterinary clinics (3.66%) respectively by coproscopic analysis. A total of 51 cats were obtained from city councils and subjected to post-mortem examination. The bile was examined for ova detection and the liver was sliced and the presence of adult flukes were observed. Twelve stray cats (23.53%) were found positive for Platynosomum sp. infections. The study observed several histopathology signs associated with platynosomiasis including hepatic steatosis, distended biliary duct, biliary duct hyperplasia and inflammation with the presence of inflammatory cells. For molecular characterization, one adult fluke per positive cats (n = 12) were selected and subjected for DNA extraction, amplification of ITS1 and cox1 gene and sequencing. Based on phylogenetic analysis, most of the sequence of ITS1 and cox1 gene were similar to each other and were grouped in a clade. More variation was observed in the cox1 sequence compared to the ITS1 sequence based on haplotype and nucleotide diversity. Based on the sequence analysis, the P. fastosum Malaysian, Vietnam and P. illiciens Brazilian isolates most likely are conspecific. The findings obtained from this study presented the detection of P. fastosum among client-owned, shelters and stray cats in Klang Valley, Malaysia, as well as providing additional molecular knowledge on P. fastosum as a reference for future molecular characterization studies.